Filosofi Manajemen : Perbandingan Budaya Kerja di Indonesia dengan Timor Leste - Wulan Saraswati; Abdul Wahid Mahsuni; Mimbha Nur Indahsari; Denilson Pereira Lay; Ade Kafa Bih (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Work culture plays an important role in determining effectiveness, productivity and collaboration in an organization. This article explores the differences and similarities of work cultures in Indonesia and Timor-Leste. Utilizing a literature review and secondary data, this research highlights the factors that influence the work cultures of both countries, the relevance of applying their respective work cultures, as well as suggestions for improving adaptability and harmony across work cultures. The research also offers insights into how cultural differences can be integrated to support more effective cross-cultural collaboration, particularly in the Southeast Asian regional context